Admission Lower Serum Phosphate Ion Levels Predict Acute Hydrocephalus of Aneurysmal Subarachnoid Hemorrhage - Zhang, Yibin; Zheng, Shufa; Wang, Haojie; Chen, Guogong; Li, Chunwang; Lin, Yuanxiang; Yao, Peisen; Kang, Dezhi (Frontiers in Neurology, 2022)
Introduction: The relationship between serum phosphate ion (sPi) and the occurrence of acute hydrocephalus (aHCP) in aneurysmal subarachnoid hemorrhage (aSAH) remains largely unknown and controversial. The primary aim of this study was to investigate the association between sPi on admission and aHCP following aSAH. Methods: The study included 635 patients over the age of 19 years diagnosed with aSAH in our institution from September 2012 to June 2018. Data on clinical characteristics, laboratory parameters, treatments, and outcomes were collected and analyzed. The association between lower sPi levels and aHCP was assessed in univariate and multivariate analyses. Propensity-score matching (PSM) analysis was performed to reduce significant differences in baseline characteristics between the aHCP group and non-HCP group. Results: The overall incidence of aHCP following aSAH was 19.37% (123/512). Lower sPi levels were detected in patients with aHCP compared with those without [0.86 (0.67–1.06) vs. 1.04 (0.84–1.21) mmol/L] in the univariate analysis. In the multivariate analysis, lower sPi level, high modified Fisher (mFisher) grade, and high Hunt-Hess grade were associated with aHCP [odds ratios (OR) 1.729, 95% confidence interval (CI) 1.139–2.623, p = 0.01; mFisher OR 0.097,95% CI 0.055–0.172, p < 0.001; Hunt-Hess, OR 0.555, 95% CI 0.320–0.961, P = 0.036]. After PSM, the matched aHCP group had a significantly lower sPi level than the matched non-aHCP group [0.86 (0.67–1.06) vs. 0.94 (0.76–1.12) mmol/L, p = 0.044]. The area under the curve (AUC) of the sPi level and the logistic regression model based on these predictors (sPi, Hunt-Hess grade, and mFisher grade) was 0.667 and 0.840 (sensitivity of 88.6% and specificity of 68.4%) for predicting aHCP, respectively. Conclusions: Lower sPi levels predict the occurrence of aHCP, and the model constructed by sPi levels, Hunt-Hess grade, and mFisher grade markedly enhances the prediction of aHCP after aSAH.